1999
DOI: 10.1002/jbmr.5650140203
|View full text |Cite
|
Sign up to set email alerts
|

Cell biology of paget's disease

Abstract: Paget's disease is characterized by markedly increased osteoclast formation and bone resorption followed by excessive new bone formation. Osteoclasts in Paget's disease are increased both in number and size, contain paramyxoviral-like nuclear inclusions, and can have up to 100 nuclei per cell. Marrow culture studies have identified several abnormalities in osteoclast formation in Paget's disease. Osteoclast-like multinucleated cells formed more rapidly in marrow cultures from patients with Paget's disease, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
0
35
0
2
Order By: Relevance
“…Similarly, there was no difference in the number of circulating osteoclast precursors in osteoporosis patients and normal controls, but osteoclasts formed from PBMs of osteoporosis patients exhibited substantially increased resorptive activity relative to normal controls [100]. Abnormally increased osteoclast formation and activity is also a characteristic feature of Paget's disease [101]. By in vitro differentiation of PBMs into osteoclasts, it was found that PBMs from Paget's patients can give rise to a significantly higher number of osteoclasts and increased bone resorption activity than PBMs from gender-and age-matched normal controls [102].…”
Section: Using Pbms As a Working Cell Model To Study For Bone Diseasesmentioning
confidence: 92%
“…Similarly, there was no difference in the number of circulating osteoclast precursors in osteoporosis patients and normal controls, but osteoclasts formed from PBMs of osteoporosis patients exhibited substantially increased resorptive activity relative to normal controls [100]. Abnormally increased osteoclast formation and activity is also a characteristic feature of Paget's disease [101]. By in vitro differentiation of PBMs into osteoclasts, it was found that PBMs from Paget's patients can give rise to a significantly higher number of osteoclasts and increased bone resorption activity than PBMs from gender-and age-matched normal controls [102].…”
Section: Using Pbms As a Working Cell Model To Study For Bone Diseasesmentioning
confidence: 92%
“…16,17) In particular, irregularity of the geometry of osteoclast resorption cavities has been demonstrated in Paget s disease 17) and glucocorticoid-induced osteoporosis. 19) Since these skeletal disorders display an increased resorption activity which is attributable to alterations in osteoclast biology, 20,21) insights into the association of osteoclast biology, geometry of osteoclastic resorption cavities, and microstructure of newly formed bone should be helpful to understand the mechanisms responsible for the maintenance of bone quality in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Paget's disease is characterized by uncontrolled bone remodeling due to increased bone resorption by osteoclasts (97). A hyperosteoclastogenic bone marrow microenvironment due to abnormal production of or response to cytokines (IL-6) and hormones [1,25(OH) 2 D 3 ], perhaps triggered by the presence of paramyxoviral-like nuclear inclusions, has been suggested as a potential mechanism (97). Only recently, enhanced RANKL expression was observed in a bone marrow stromal cell line developed from a patient with Paget's disease (98).…”
Section: Drug-induced Osteoporosismentioning
confidence: 99%